Snacking At School Increased The Risk Of Overweight/Obesity In Children - Aulia Jauharun Nisak; Trias Mahmudiono (Universitas Airlangga, 2017)
Child obesity is one of the most serious public health problems of the 21st century. Poor eating habits such as excessive eating high in fat, sugar, and calories and lack of physical activity are the causes of overweight or obesity in children. This study aims to analyze the relationship between patterns of consumption of snacks with overweight/obesity. The study was conducted at Ploso I-172 Public Elementary School, Tambaksari District, Surabaya in May-July 2017 with a case-control design. The method of data collection is done by interview and anthropometric measurements. The sample size was 112 respondents with ratio of case and control is 1: 1. Data analysis using linear regression and logistic regression tests. The results showed that snack foods that were consumed by children were fruit syrup, flavored drinks, chocolate, papeda, fried foods, brains and sausages, meatball, syrup, sauce, and toppings. There is a significant relationship between the consumption of daily frequency snack food include fruit syrup (p = 0.004; OR = 8,000), flavored drinks (p = 0.02; OR = 13,412), chocolate (p = 0.013; OR = 6.333), fried foods (p = 0.015; OR = 14.786), brains and sausages (p = 0.004; OR = 8.750), meatball (p = 0.039; OR = 4.044), syrup, sauce, and toppings (p = 0.023; OR = 4.643 ) with the incidence of overweight / obesity. The conclusion in this study is that there is a correlation between the pattern of consumption of snacks with overweight/obesity in school children. Research suggestions, parents, and schools need to pay attention to the selection of good and nutritious snacks for preventing overweight and obesity in children.